Membrane Condensation and Curvature Induced by SARS-CoV-2 Envelope Protein - Wölk, Christian (Langmuir : the ACS journal of surfaces and colloids, 2024)
The envelope (E) protein of SARS-CoV-2 participates in virion encapsulation and budding at the membrane of the endoplasmic reticulum Golgi intermediate compartment (ERGIC). The positively curved membrane topology required to fit an 80 nm viral particle is energetically unfavorable; therefore, viral proteins must facilitate ERGIC membrane curvature alteration. To study the possible role of the E protein in this mechanism, we examined the structural modification of the host lipid membrane by the SARS-CoV-2 E protein using synchrotron-based X-ray methods. Our reflectometry results on solid-supported planar bilayers show that E protein markedly condenses the surrounding lipid bilayer. For vesicles, this condensation effect differs between the two leaflets such that the membrane becomes asymmetric and increases its curvature. The formation of such a curved and condensed membrane is consistent with the requirements to stably encapsulate a viral core and supports a role for E protein in budding during SARS-CoV-2 virion assembly